Rethinking Water Governance in the Saskatchewan River Delta Through Indigenous Relational Worldviews - John Bosco Acharibasam; Kathryn Riley; Ranjan Datta; Elder Denise McKenzie; Elder Veronica Favel (Australian Journal of Environmental Education)
This study critically examines the implications of integrating Indigenous relational worldviews into the water governance framework of the Saskatchewan River Delta. Using a relational theoretical framework and community-based participatory research methodology, both Indigenous community members and non-Indigenous researchers collectively examine the negative impacts of Western water governance policies and practices on the Métis community residing in Cumberland House, located in northeast Saskatchewan, Canada. Through Indigenous traditional water story-sharing methods with Indigenous Elders and Knowledge Keepers, our focus centres on Indigenous interpretations and ways of knowing the Delta. The community highlighted the pervasive influence of power dynamics and political agendas in the governance of the Delta. As such, we emphasise the necessity of challenging settler colonial systems and structures and reinvigorating Indigenous worldviews for water governance. By doing so, we advocate for the advancement of Indigenous sovereignty and self-determination in their relationship with land and water, thereby promoting the meaningful implications of the Truth and Reconciliation Commission Calls to Action.